2011
DOI: 10.1121/1.3641455
|View full text |Cite
|
Sign up to set email alerts
|

Excitation threshold for subharmonic generation from contrast microbubbles

Abstract: Six models of contrast microbubbles are investigated to determine the excitation threshold for subharmonic generation. The models are applied to a commercial contrast agent; its characteristic parameters according to each model are determined using experimentally measured ultrasound attenuation. In contrast to the classical perturbative result, the minimum threshold for subharmonic generation is not always predicted at excitation with twice the resonance frequency; instead it occurs over a range of frequencies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
68
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(74 citation statements)
references
References 44 publications
6
68
0
Order By: Relevance
“…37 It was shown that for models incorporating a strain softening encapsulation, subharmonic thresholds were minimum around f T /f 0 % 1. A recent study investigating the size-dependent subharmonic response of Target-Ready MicroMarker at 11 MHz has shown that bubble diameters of approximately 2.6 lm emit the largest subharmonic amplitude.…”
Section: B Shell Elasticitymentioning
confidence: 99%
See 1 more Smart Citation
“…37 It was shown that for models incorporating a strain softening encapsulation, subharmonic thresholds were minimum around f T /f 0 % 1. A recent study investigating the size-dependent subharmonic response of Target-Ready MicroMarker at 11 MHz has shown that bubble diameters of approximately 2.6 lm emit the largest subharmonic amplitude.…”
Section: B Shell Elasticitymentioning
confidence: 99%
“…(6), this suggests that Target-Ready MicroMarker is characterized by a minimum subharmonic threshold around f T /f 0 % 1, consistent with a strain softening encapsulated bubble. 37 For Definity, no clear relationship between shell elasticity and resting diameter or maximum strain is present it is reasonable to also consider modeling a shell elasticity dependence on initial diameter from the beginning of the derivation presented in the above sections. Indeed, sizedependent elasticity has been presented before, with physical rationale based in phospholipid condensation state 21 or sizedependent shell thickness.…”
Section: B Shell Elasticitymentioning
confidence: 99%
“…27 The damped natural frequency for unforced oscillations, x d , is related to the eigenfrequency of the system by the damping coefficient,…”
Section: Estimation Of the Shell Viscositymentioning
confidence: 99%
“…For example, it has been previously reported that increasing the shear viscosity of the agent increases the threshold for subharmonic oscillations. 44 Changing the shell stiffness enhances the resonance frequency of the agent, and alters the range of sizes of bubbles that demonstrate the strongest nonlinear oscillations. 44 Two other parameters-the buckling-radius and break-up radiusare reported to strongly impact the predicted nonlinear response of the agent.…”
Section: Discussionmentioning
confidence: 99%
“…44 Changing the shell stiffness enhances the resonance frequency of the agent, and alters the range of sizes of bubbles that demonstrate the strongest nonlinear oscillations. 44 Two other parameters-the buckling-radius and break-up radiusare reported to strongly impact the predicted nonlinear response of the agent. 13, 45 Sun and colleagues have shown previously that choosing buckling and rupture radii close to the resting radius of the microbubble results in a stronger nonlinear response.…”
Section: Discussionmentioning
confidence: 99%